Europe's long march to a unified takeover regulation: the 13th company law directive on takeover bids - quo vadis? - Meyer, Julia (Department of Commercial Law, 2026)
The global financial markets are subject to lasting and far-reaching structural changes. One consequence of these changes are the increasing number and growing impact of company takeovers and mergers worldwide 1. Accordingly, European takeover activity has experienced an enormous increase in the last years. In 1999, deals involving European firms added up to US-$ 1.5 trillion, more than twice as much as the previous year. For the first time since the beginning of the 1990s, Europe reached a higher volume of deals than America2. The main reasons for the global increase of takeovers and mergers are technical changes, especially in the field of communication and information technology. As a result, markets are growing together and national boundaries play a less significant role to the economic activity of corporate enterprises 3. In Europe, this process is encouraged by the adoption of a single market with a single currency. As the single market develops, domestic sectors such as banking and retailing are confronted with a growing pressure to strike out across the continent, motivated by obtainable cost advantages as well as by the fear of being overtaken by rivals and so disappointing investors. The euro has allowed investors to become much more flexible. The mobility of capital causes higher competition amongst companies seeking for investors' attention. Currency concerns do not affect investment decisions within the Community any more4.